Regulating Interfacial Chemistry in Lithium‐Ion Batteries by a Weakly Solvating Electrolyte - Yao, Yu‐Xing; Chen, Xiang; Yan, Chong; Zhang, Xue‐Qiang; Cai, Wen‐Long; Huang, Jia‐Qi; Zhang, Qiang (Angewandte Chemie International Edition, 2021)
The performance of Li‐ion batteries (LIBs) is highly dependent on their interfacial chemistry, which is regulated by electrolytes. Conventional electrolyte typically contains polar solvents to dissociate Li salts. Herein we report a weakly solvating electrolyte (WSE) that consists of a pure non‐polar solvent, which leads to a peculiar solvation structure where ion pairs and aggregates prevail under a low salt concentration of 1.0 M. Importantly, WSE forms unique anion‐derived interphases on graphite electrodes that exhibit fast‐charging and long‐term cycling characteristics. First‐principles calculations unravel a general principle that the competitive coordination between anions and solvents to Li ions is the origin of different interfacial chemistries. By bridging the gap between solution thermodynamics and interfacial chemistry in batteries, this work opens a brand‐new way towards precise electrolyte engineering for energy storage devices with desired properties. A weakly solvating electrolyte affords a new path towards anion‐derived interfacial chemistry in lithium‐ion batteries. By formulating electrolyte with a non‐polar solvent, ion pairs and aggregates prevail under normal concentrations and give rise to anion‐derived interphases on graphite electrodes with superior electrochemical performances.